Potential impacts of nanoparticles integration on micropropagation efficiency: current achievements and prospects - Guru, Gurudayal Ram; Ramteke, Pramod W.; Veres, Csilla; Vágvölgyi, Csaba (Frontiers in Plant Science, 2025)
The use of nanoparticles (NPs) in plant tissue culture systems represents a new approach to improve the efficiency of micropropagation. Owing to their nanoscale size, high surface area concomitant with volume, and controllable and targeted release, researchers have tested the experimental benefits of NPs in various ways during each phase of in vitro propagation, which include enhancing surface sterilization to reduce microbial contamination, the targeted uptake of specific macro-and micronutrients, regulating plant hormonal activity to enhance callogenesis, increased shoot multiplication and rooting, and increasing the survival rate during acclimatization. In addition, some situations where NPs are applied can reduce oxidative stress and regulate hormonal pathways, which will stabilize the physiological state of the plant and support better developmental integrity of the regenerating plantlets. In moving forward with the application of nanoparticles, the major limiting factors are nanotoxicity, persistence in the environment, species specificity, and the lack of an established regulatory framework. In this review, the recent published successes in NP-mediated micropropagation are summarized, how they impart their effects in plant science at the cellular and molecular levels are explained, and potential future innovations such as green-synthesized nanomaterials and new smart delivery platforms are also identified. Realizing the full potential of nanotechnologies for application with micropropagation will be critical for developing scalable, sustainable, and precision agricultural production systems.